OPTIMIZATION OF VCO LOTION PREPARATIONS WITH VARIATIONS CETYL ALCOHOL AND CARRAGEEN CONCENTRATIONS USING SLD METHOD - Sabiti, Farroh Bintang; Sholeh, Aries Badrus; Musyayadah, Zahrotul (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Lotion is a cosmetic preparation of an emollient group that contains a large amount of water. This formulation possesses several properties, namely, as a source of moisture for the skin, providing an oily layer that makes the hands and body soft. VCO is utilized as a natural skin moisturizer to prevent tissue damage and protect the skin. VCO has a very high moisture content, which prevents skin dryness. A lotion was formulated with an emulsifying agent to stabilize the emulsion system. One of the constituent ingredients of the lotion is cetyl alcohol, which functions as an emulsifying agent. Cetyl alcohol can be substituted by carrageenan, which serves the same function with the added benefit of being a humectant. The aim of this study was to identify the formulation of VCO lotion and to investigate the effect of different concentrations of the emulsifying agents cetyl alcohol and carrageen on physical evaluation tests, namely organoleptic tests, homogeneity tests, spreading tests, pH tests, adhesion tests, emulsion type tests, and viscosity tests in lotion formulations. An experimental method was employed in this study. The research was carried out by making lotions from various ingredients containing the active ingredient VCO at a concentration of 7%, as well as varying concentrations of cetyl alcohol (range 2-5%) and carrageenan (range 1-3%) as an emulsifying agent and additional ingredients for the preparations whose optimization had been determined using the simplex lattice design method ...